Antioxidant Flavonoid Metabolites of Mukia maderaspatana (L.) M. Roemer leaves - Petrus, A.J.A.; Bhuvaneshwari, N. (Asian Journal of Chemistry, 2011)
Mukia maderaspatana (Linn.) M. Roemer, (Family: Cucurbitaceae) is an indigenous leafy vegetable, reported to offer protection against a number of oxidative stress-mediated ailments. Earlier studies have brought to light the total phenolic contents, reactive species (ROS/RNS) scavenging and metal chelating capacities of the leaf extract. 2,2'-Azino-bis(3-ethylbenzothiazoline-6-sulphonate (ABTS•+), super oxide (O2•−) and NO scavenging capacities, ferric-reducing antioxidant power (FRAP) and ferrous chelating capacities of six C-glucoflavones, isolated and characterized from the edible leaves have been evaluated. 6-C-b-D-glucopyranosylluteolin (4) and 8-C-b-Dglucopyranosylluteolin (6) exhibited maximum ROS/RNS scavenging capacities, while the predominant flavone of the leaf, 7-O-b-D-glucopyranosyl-6-C-b-D-glucopyranosylapigenin (2) fared weakly. 6-C-b-D-glucopyranosylapigenin (3) was found to be a better scavenger of ABTS•+ whereas 8-C-b-D-glucopyranosylapigenin (5) scavenged O2•− better and 7-O-b-D-glucopyranosyl-6-C-b-D-glucopyranosylluteolin (1) scavenged NO better, in addition to possessing a good ferricreducing antioxidant power. The ferrous chelating capacities were in the order 1 > 6 > 4 > 2 > 5 > 3, depending upon the metal-binding motifs of their molecular structures. 1, 4 and 6 were found to be only 10 % less potent to chelate Fe(II) compared to deferoxamine, the hydroxamic siderophore, widely employed in the treatment of patients constantly submitted to blood transfusion. The potential ROS/RNS scavenging and metal chelating antioxidant capacities of the C-glucoflavones may contribute considerably to the total antioxidant capacity as well as to the reported protective properties of this functional leafy vegetable.